From objections to KNA to a case for a hearer-centered norm of assertion - Ferreira Filho, João B. (Sofia, 2025)
An assertion is generally understood as a speech act in the form of a statement meant to impart something of epistemic significance: we assert to clarify, inform, teach, and improve a hearer’s epistemic status. Epistemologist Timothy Williamson (1996) claims that the nature of assertion is intrinsically normative: assertion has a constitutive norm. That norm, according to Williamson, is that the asserter ought to know the content of the assertion (the “knowledge norm of assertion” or “KNA”). In this paper, I examine (a) Williamson’s argument for a constitutive norm of assertion and (b) whether that norm must be knowledge. I will argue, particularly through Jennifer Lackey’s famous case of the creationist teacher, that an asserter can – and often does – consistently impart something of epistemic significance to a hearer without fully satisfying the KNA. I conclude with a recommendation that KNA, albeit an intuitive expectation about asserters, is not a necessary condition for assertion in epistemically successful assertoric practices.